Effect of Layer Thickness in Selective Laser Melting on Microstructure of Al/5 wt.%Fe2O3 Powder Consolidated Parts. (6th January 2014) - Dadbakhsh, Sasan; Hao, Liang
Abstract : In situ reaction was activated in the powder mixture of Al/5 wt.%Fe2 O3 by using selective laser melting (SLM) to directly fabricate aluminium metal matrix composite parts. The microstructural characteristics of these in situ consolidated parts through SLM were investigated under the influence of thick powder bed, 75  μ m layer thickness, and 50  μ m layer thickness in various laser powers and scanning speeds. It was found that the layer thickness has a strong influence on microstructural outcome, mainly attributed to its impact on oxygen content of the matrix. Various microstructural features (such as granular, coralline-like, and particulate appearance) were observed depending on the layer thickness, laser power, and scanning speed. This was associated with various material combinations such as pure Al, Al-Fe intermetallics, and Al(-Fe) oxide phases formed after in situ reaction and laser rapid solidification. Uniformly distributed very fine particles could be consolidated in net-shape Al composite parts by using lower layer thickness, higher laser power, and lower scanning speed. The findings contribute to the new development of advanced net-shape manufacture of Al composites by combining SLM and in situ reaction process.